Antagonistic Interaction Between Piper betle and Peperomia pellucida Ethanolic Extracts Reduces Antibacterial Activity Against Cutibacterium acnes - Heny Buwe Leo; Tadeus Andreas Lada Regaletha; Cahyani Purnasari; Nurul Fatmawati Pua Upa (Inspire Global Insight Journal, 2026)
Acne vulgaris is a chronic inflammatory disorder of the pilosebaceous unit in which Cutibacterium acnes plays a central pathogenic role. Rising resistance of C. acnes to conventional antibiotics such as clindamycin has intensified interest in plant-derived alternatives. This study aimed to evaluate the antibacterial activity of combined ethanolic extracts of green betel leaf (Piper betle) and pepper elder leaf (Peperomia pellucida) against C. acnes and to determine the combination ratio with the strongest antibacterial effect. A true experimental, post-test-only control group design was used. Leaves were macerated in 95% ethanol (1:10, w/v) for three days. Seven treatment groups were tested by the Kirby-Bauer disc diffusion method: single extract of P. betle 15%, single extract of P. pellucida 15%, combinations at ratios of 1:1, 1:2, and 2:1 at a fixed total concentration of 15%, a positive control (standardized clindamycin disc), and a negative control (sterile distilled water). Each group was replicated four times, determined using the Federer formula. Zones of inhibition were measured with a caliper after 24 h of incubation at 37 °C. Data were analyzed with Shapiro-Wilk, Levene's, one-way ANOVA, and Tukey's HSD post-hoc tests (α = 0.05). All extract treatments inhibited C. acnes growth. The single P. betle 15% extract produced the largest inhibition zone among plant treatments (12.19 ± 0.44 mm, strong category), whereas single P. pellucida 15% extract produced 8.96 ± 0.30 mm (moderate category). Combination ratios of 1:1, 1:2, and 2:1 produced inhibition zones of 9.57 ± 0.77 mm, 8.76 ± 0.39 mm, and 8.56 ± 0.73 mm, respectively, all within the moderate category. The positive control produced 27.19 ± 0.95 mm (very strong), while the negative control produced no inhibition zone. One-way ANOVA revealed a statistically significant difference among treatment groups (p < 0.001), and Tukey's HSD indicated that the combinations did not significantly exceed the single P. pellucida extract, while the single P. betle extract significantly outperformed all combination ratios. Combined ethanolic extracts of P. betle and P. pellucida exhibit antibacterial activity against C. acnes, but combination did not enhance efficacy beyond that of the single P. betle extract, suggesting an antagonistic rather than synergistic interaction. The 1:1 ratio was the most effective among the combinations tested.